Contextualizing Differentiated Instruction in Islamic Education: An Information Processing Approach in Indonesian Secondary Schools - Dina Mardiana; Umiarso Umiarso; Samsoo SA-U (Pedagogy Review, 2026)
The reality of implementing differentiated learning within the Merdeka  Curriculum is increasingly evident nowadays. This requires a contextual-adaptive response from all elements of the subject area, including Islamic Religious Education. This study aims to explore a contextualized differentiated instruction model for Islamic Religious Education  within the Merdeka  Curriculum in three Indonesian secondary schools. The study used an exploratory, sequential, mixed-methods design. In the first stage, qualitative data were collected through interviews, observations, and document analysis. This was done to identify actual practices of differentiated  instruction and to construct a prototype model. In the second stage, quantitative data were collected from 96 respondents, consisting of teachers and students. A closed-ended questionnaire was used to describe their perceptions of the implementation of differentiated instruction. The instrument represented four dimensions: content differentiation, process differentiation, product differentiation, and inclusive learning environment. Content validity was established through expert judgment. Reliability testing yielded a Cronbach’s Α of 0.642, which indicates limited but usable internal consistency for an exploratory study. Interpretation should therefore be cautious. The findings show that differentiated  instruction in the three schools was implemented through systematic planning, varied instructional practices, and continuous evaluation. The qualitative synthesis identified four core components of the proposed model: initial assessment, flexible planning, varied implementation, and continuous evaluation. Quantitative findings further indicate that respondents generally perceived the implementation of differentiated  positively across the four dimensions. This research contributes a contextual model of differentiated  instruction and highlights the need for further research with stronger instruments and broader samples.                                       Keywords: Differentiated instruction, Merdeka  curriculum, Islamic religious education, Secondary school students.